Oseltamivir no tratamento da gripe sazonal na grávida - qual a evidência? - Baía,Catarina (2021)
Abstract Overview/Aims: Flu increases maternal and fetal complications. Studies recommend the use of neuraminidase inhibitors to treat influenza in pregnant women. This review aims to analyse the evidence about oseltamivir’s effectiveness in the treatment of seasonal flu. Methods: Literature research was conducted in the MEDLINE, DARE, Cochrane, Web of Science, TRIP and NICE, and guidelines databases using the query: “(Treat* OR Therapy) AND (oseltamivir OR neuraminidase inhibitors) AND pregnan*”. Results: Two systematic reviews and eight guidelines were analyzed in this review. Conclusion: Oseltamivir appears to be effective in treatment of seasonal influenza in pregnant women - Strength of Recommendation B.